2014
DOI: 10.2139/ssrn.2511192
|View full text |Cite
|
Sign up to set email alerts
|

Price Versus Quantities Versus Indexed Quantities

Abstract: We develop a stochastic model to rank different policies (tax, fixed cap and relative cap) according to their expected total social costs. Three types of uncertainties are taken into account: uncertainty about abatement costs, businessas-usual (BAU) emissions and future economic output (the two latter being correlated). Two parameters: the ratio of slopes of marginal benefits and marginal costs, and the above-mentioned correlation, are crucial to determine which instrument is preferred.When marginal benefits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…and Newell and Pizer (2003) argue that the slope of the MD function tends to be small for stock pollutants, because the flow is much smaller than the stock level. 14 Newell and Pizer (2008), Jotzo and Pezzey (2007), and Branger and Quirion (2014) assume that c 2 d 2 , although they do not provide estimates of the explicit magnitudes of the difference. Ackerman and Bueno (2011) compares the estimated marginal abatement costs for a number of nations from different models and shows that the slope of MAC differs across nations and models and tends to be increasing as the abatement level rises.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Newell and Pizer (2003) argue that the slope of the MD function tends to be small for stock pollutants, because the flow is much smaller than the stock level. 14 Newell and Pizer (2008), Jotzo and Pezzey (2007), and Branger and Quirion (2014) assume that c 2 d 2 , although they do not provide estimates of the explicit magnitudes of the difference. Ackerman and Bueno (2011) compares the estimated marginal abatement costs for a number of nations from different models and shows that the slope of MAC differs across nations and models and tends to be increasing as the abatement level rises.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…There is a large and growing literature on intensity instruments, that is, caps imposed on emission intensities of individual firms, similar to firm level emission taxes and standards (see, for example, Ebert (1998), Fischer (2003, Quirion (2005), Fischer and Fox (2007), Jotzo and Pezzey (2007), Newell and Pizer (2008), Webster, Wing and Jakobovits (2010), Fischer and Springborn (2011), Holland (2012), Branger and Quirion (2014), and Caparros, Just and Zilberman (2015)). 2 Intensity instruments are a special form of performance standards and have been adopted to regulate firm emission, such as in the lead phase-out program of the United States during the 1980s and in cases of state level renewable portfolio standards that require utilities to have certain percentages of total electricity generated from renewable sources (Lyon (2016)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellerman and Montero, 2007) as a way to smooth market shocks. More recently, Newell and Pizer (2008) and Branger and Quirion (2014) propose to index the allocation of permits to any exogenous variable, such as GDP, that could be correlated to shocks affecting permit prices. And in the specific context of the carbon market in the EU, there are proposals to introduce a market stability reserve from or to which auctioned permits could be withdrawn or add as the number of unused (i.e., banked) permits in the market reaches a critical level that could push permit prices either too high or too low (Kollenberg and Taschini, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Models for multipolicy, multicountry analyses have been developed; for example, Branger and Quirion use a stochastic model to rank different policies according to their expected total social costs [20]. They found that a tax is preferred to caps, and relative caps are preferred to fixed caps in the US and emerging countries, whereas a fixed cap is a better choice over a relative cap in Europe and Japan.…”
mentioning
confidence: 99%